Meningkatkan Hasil Belajar Dan Keterampilan Berpikir Kritis Siswa Muatan PKN Menggunakan Model Lebah - Latifah, Nur; Rafianti, Wahdah Refia (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The research problem is low learning outcomes and critical thinking skills. The reason is that students find it difficult to understand concepts, learning is monotonous, less involved, slow to think and teachers have not used varied models. Efforts to overcome this with the "LEBAH" model (Problem Based Learning, Example Non Example & Make A Match). The purpose of this study is to describe teacher activity, to analyze the increase in student activity, learning outcomes and critical thinking skills. Qualitative and quantitative approaches. CAR is carried out in 4 meetings, class IV B at SDN Manarap Lama 1, 23 students in 2022/2023. Qualitative data analysis techniques observation sheet activities of teachers, students and critical thinking skills, while quantitative data measures learning outcomes. The results show that the teacher's activity gets 100%. Student activity gets 100%. Cognitive learning outcomes get 96%, affective get 96% and psychomotor get 96%. Critical thinking skills gain 96%. Based on the results of the study, it was concluded that the LEBAH model can improve learning outcomes and critical thinking skills. It is suggested that this model be used as an alternative to improve learning outcomes and critical thinking skills.